Predictive effect of preoperative abdominal and emotional aura on temporal lobe epilepsy surgery (Annals of Medical Research, 2024)
Aim: Temporal lobe epilepsy surgery is the most common type of epilepsy surgery. This study evaluates the relationship between preoperative auras and surgical prognosis.Materials and Methods: The follow-up data of 100 patients who underwent anterior temporal lobectomy surgery after 2 years was reviewed. The patients were divided into two groups based on the presence or absence of abdominal-emotional (AE) aura. Each patient was evaluated with a detailed history, video-electroencephalography (EEG), neuroimaging, and postsurgical outcomes according to Engel classification to predict postsurgical seizure freedom.Results: After 2 years of follow-up, 71 patients were seizure-free. Based on aura types, univariate analysis showed that the age of disease onset and history of febrile convulsion were higher in the AE (+) group (p=0.013, p
Keywords: Temporal lobe epilepsy; Aura; Epilepsy surgery